Akad Ijarah Dalam Perspektif Fuqaha Serta Relevansinya Terhadap Perkembangan Ekonomi - Hardiati, Neni; F, Fitriani; Kusmawati, Tia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The practice of ijarah or rent has been commonly carried out by earlier humans, this is in the Qur'an, namely QS. Al-Baqarah verse 233, QS. At-Thalaq verse 6, then QS. al-Qasas verses 26 and 27, and the Hadith related to it. There is discussion on this subject in the sources of Islamic law, namely the Qur'an and Hadith, indicating that the lease transaction is important in its application to meet the economic needs of mankind. Fiqh scholars differ in expressing opinions on ijarah, therefore this paper seeks to describe the concept of ijarah according to the fuqaha and how the development of the ijarah contract in the Islamic finance industry in the form of ijarah vomitiya bittamlik (IMBT) products or commonly known as lease purchase . The type of research used in this study is descriptive literature, where research is carried out by collecting books, searching the internet and scientific works needed to be studied, so that it can be seen how the concept of ijarah for fuqaha and its relevance to economic development can be known. The results of this study conclude that although they differ in expressing opinions about ijarah, all of them have the same meaning and purpose, namely agreements on the properties of objects to other people in exchange for certain payments and conditions. For many scholars, ijarah is a common contract, a kind of buying and selling.